Effect of dispersion of CdSe quantum dots on phase transition, electrical and electro-optical properties of 4PP4OB. Issue 8 (20th June 2016) - Singh, U. B.; Pandey, M. B.; Dhar, R.; Verma, R.; Kumar, S.
ABSTRACT: We prepared composites of a liquid crystalline material, 4-pentylphenyl 4-octyloxybenzoate (4PP4OB) and cadmium selenide quantum dots (CdSe-QDs) and investigated their thermodynamic, electro-optical and dielectric properties. The effect of QDs on transition temperature from isotropic to nematic and nematic to smectic A phases was evaluated in this study. The effect of CdSe-QDs inclusion on various display parameters on host liquid crystals was studied in the nematic phase. The electrical parameters of the composites – relative permittivity, dielectric anisotropy, dielectric loss and dielectric relaxation – were investigated in the nematic and smectic phases. The changes in dielectric parameters of the composites are explained in terms of Maier–Meier theory. GRAPHICAL ABSTRACT: